2016
DOI: 10.18632/oncotarget.10117
|View full text |Cite
|
Sign up to set email alerts
|

P300 inhibition enhances gemcitabine-induced apoptosis of pancreatic cancer

Abstract: The transcriptional cofactor p300 has histone acetyltransferase activity (HAT) and has been reported to participate in chromatin remodeling and DNA repair. We hypothesized that targeting p300 can enhance the cytotoxicity of gemcitabine, which induces pancreatic cancer cell apoptosis by damaging DNA. Expression of p300 was confirmed in pancreatic cancer cell lines and human pancreatic adenocarcinoma tissues by western blotting and immunohistochemistry. When pancreatic cancer cells were treated with gemcitabine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 29 publications
(36 reference statements)
3
38
0
Order By: Relevance
“…We have previously shown that the two HAT inhibitors, ICG-001 and C646, differentially impair the global gene expression levels in human pancreatic and colorectal cancer cell lines [37]. Additionally, other work has shown that ICG-001 and C646 reduce tumorigenicity of pancreatic cancer cell models [38][39][40] and ICG-001 has been used in clinical trials for pancreatic cancer (NCT01302405). However, the impact of HAT inhibitor treatment on histone acetylation remains unknown.…”
Section: Histone Acetyltransferase Inhibitors Alter Global H3k27ac Anmentioning
confidence: 99%
“…We have previously shown that the two HAT inhibitors, ICG-001 and C646, differentially impair the global gene expression levels in human pancreatic and colorectal cancer cell lines [37]. Additionally, other work has shown that ICG-001 and C646 reduce tumorigenicity of pancreatic cancer cell models [38][39][40] and ICG-001 has been used in clinical trials for pancreatic cancer (NCT01302405). However, the impact of HAT inhibitor treatment on histone acetylation remains unknown.…”
Section: Histone Acetyltransferase Inhibitors Alter Global H3k27ac Anmentioning
confidence: 99%
“…Furthermore, the expression of leptin in gastro-esophageal adenocarcinomas was associated with chemoresistance. The use of leptin receptor antagonist SHLA increased the sensitivity to Cisplatin in the resistant gastric cancer cell line, AGS Cis5, and the oesophageal adenocarcinoma cell line, OE33[134]. …”
Section: Pancreatic Cancer Stem Cellsmentioning
confidence: 99%
“…However, P300 overexpression was not significantly associated with OS. Although P300 has been observed as a tumour suppressor in the majority of studies, its oncogenic role has also been confirmed in multiple cancer types, where it is involved in the EMT (23,27,28), proliferation (29,30) and apoptosis (30,31). Gao et al (16) suggested that high expression of P300 enhanced EMT of HCC cells, and Liao et al (27) also indicates that P300 promotes EMT in an NPC cell line.…”
Section: Discussionmentioning
confidence: 99%
“…Inagaki et al (29), indicated that core-binding protein/P300 histone acetyltransferase activity is responsible for epigenetic regulation of proliferation and invasion in HCC cells, and Dou et al (32) suggested that midazolam inhibits the proliferation of human head and neck SCC cells by downregulating P300 expression. Gao et al (30) reported that the P300 inhibitor C646 induces cell cycle arrest and apoptosis in acute myeloid leukemia cells and Ono et al (31) indicated that P300 inhibition enhances the gemcitabine-induced apoptosis of pancreatic cancer cells. Table IV.…”
Section: Discussionmentioning
confidence: 99%